2011
DOI: 10.1038/bjc.2011.376
|View full text |Cite
|
Sign up to set email alerts
|

A combination of serum leucine-rich α-2-glycoprotein 1, CA19-9 and interleukin-6 differentiate biliary tract cancer from benign biliary strictures

Abstract: Background:Biliary tract cancer (BTC) and benign biliary strictures can be difficult to differentiate using standard tumour markers such as serum carbohydrate antigen 19-9 (CA19-9) as they lack diagnostic accuracy.Methods:Two-dimensional difference gel electrophoresis and tandem mass spectrometry were used to profile immunodepleted serum samples collected from cases of BTC, primary sclerosing cholangitis (PSC), immunoglobulin G4-associated cholangitis and healthy volunteers. The serum levels of one candidate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 49 publications
4
56
0
Order By: Relevance
“…These results suggest the possibility of LRG as a marker for the differential diagnosis between AOSD and RA in patients presenting with polyarthritis. However, elevated serum LRG levels have been reported in patients with bacterial infection, malignancies and inflammatory bowel diseases (4,14,15). These results collectively suggest that LRG may not be a specific diagnostic marker but is a useful marker to monitor inflammatory burden in AOSD.…”
Section: Discussionmentioning
confidence: 74%
“…These results suggest the possibility of LRG as a marker for the differential diagnosis between AOSD and RA in patients presenting with polyarthritis. However, elevated serum LRG levels have been reported in patients with bacterial infection, malignancies and inflammatory bowel diseases (4,14,15). These results collectively suggest that LRG may not be a specific diagnostic marker but is a useful marker to monitor inflammatory burden in AOSD.…”
Section: Discussionmentioning
confidence: 74%
“…One study suggested a potential use in the diagnosis of bladder cancer, as increased levels were reported in the urine [30]. In another study, high levels were found in biliary tract cancer compared with cholangiocytes in benign biliary disease [31].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, owing to lack of specific clinical symptoms, CC and GBC, characterized by notorious difficulty in diagnosis, high mortality as well as poor sensitivity to conventional therapies, always advance terminal stage with serious invasion and metastasis to other organs [80,81]. It is also difficult to distinguish BTCs and benign biliary diseases by detecting the standard tumor markers such as serum carbohydrate antigen 19-9 (CA19-9) with low diagnostic accuracy [82]. Pathological diagnosis on the biopsy obtained either via endoscopic retrograde cholangiopancreatography (ERCP) or percutaneous transhepatic cholangiography (PTC) is still considered as gold standard for BTC diagnosis to certify whether the neoplasm is malignancy [83].…”
Section: Mirnas Serving As Novel Biomarkers For the Diagnosis In Btcmentioning
confidence: 98%